Design of carbonic anhydrase with improved thermostability for CO2 capture via molecular simulations. Issue 38 (May 2020) - Wu, Shenglan; Chen, Jinrui; Ma, Liang; Zhang, Kai; Wang, Xiaoxiao; Wei, Yuping; Xu, Jian; Xu, Xia
Highlights: A thermostable human CA II was developed based on molecular simulations. Replacement of Leu204 by Lys204 significantly enhances its thermosatbility. L204 K has a comparable hydratase activity as the wild type hCA II. L204 K is able to maintain its activity in the presence of anions and EDTA. L204 K is a robust and efficient biocatalyst for CO2 capture. Abstract: Chemical absorption of CO2 is the most widely used method to capture CO2 . However, high cost and slow CO2 absorption rate severely hinder its commercial utilization. Human carbonic anhydrase II (hCA II) having rapid hydratase reaction rate can potentially overcome these obstacles but being highly unstable against harsh process conditions. To enhance thermostability, a novel CA was developed based on molecular simulations. Substituting residue Leu204 with Lys has a comparable hydratase activity as the wild type (WT) hCA II, 1.98 × 10 6 s −1 for kcat and 2.36 × 10 8 M −1 s −1 for kcat /Km . Importantly, the replacement of L204 K results in higher temperature resistance with 100 % retention at 45 °C and around 50 % at 55 °C while WT totally inactivates at 45 °C. Furthermore, L204 K is able to maintain its activity in the presence of anions and EDTA. The robustness and efficiency of this novel CA make it a competitive candidate for CO2 capture.